Appropriation and invention of tradition : the East India Company and Hindu law in early colonial Bengal - Bhattacharyya-Panda, Nandini (New Delhi ; Oxford : Oxford University Press, 2008)
Investigating the intricate and dynamic links between power and knowledge in the evolution of institutions under colonial rule, this book underlines innovative ways of looking at the legal history of colonial India.
Includes bibliographical references and index.
Description based on print version record.
Keywords: East India Company -- History -- 18th century; Law -- India -- Bengal -- History -- 18th century; Customary law -- India -- Bengal -- History -- 18th century; Hindu law -- History -- 18th century; Bengal (India) -- Colonial influence